Studies on the catalytic site of rat liver HMG-CoA reductase: interaction with CoA-thioesters and inactivation by iodoacetamide. - J Roitelman; I Shechter (Journal of Lipid Research, 1989)
The localization of reactive cysteines and characterization of the HMG-CoA binding domain of rat liver HMG-CoA reductase were studied using iodoacetamide (IAAD) and short-chain acyl-CoA thioesters. Freeze-thaw-solubilized HMG-CoA reductase is irreversibly inactivated by IAAD with a second order rate constant of 0.78 M-1 sec-1 at 37 degrees C and pH 7.2. This IAAD inactivation is slowed down by pretreatment of the enzyme with disulfides, indicating that inactivation of HMG-CoA reductase occurs mainly through alkylation of specific cysteine residues in the protein. The substrate HMG-CoA, but not NADP(H), effectively protects the reductase from IAAD inactivation. When both HMG-CoA and NADP(H) are present, the reductase is inactivated by IAAD at a rate much faster than the inactivation in the presence of HMG-CoA alone. Of the two moieties of the HMG-CoA thioester, the CoA moiety confers protection from IAAD inactivation whereas HMG is totally ineffective. A series of CoA-thioesters of mono- and dicarboxylic acids of various size were tested for their effect on the activity of HMG-CoA reductase. The CoA analog, desulfo-CoA (des-CoA), and all CoA-thioesters of monocarboxylic acids of up to 6 carbons in length exhibit mixed-type inhibition of reductase activity. The competitive inhibition constants (Ki) for these compounds vary between 1 and 2 mM, whereas the noncompetitive component (K'i) is relatively constant (540 +/- 20 microM). As the acyl chain length increases beyond 6 carbons, the thioesters of monocarboxylic acids become more potent and acquire the characteristics of pure noncompetitive inhibitors. In contrast, the monothioesters of dicarboxylic acids are pure competitive inhibitors with Ki values which are similar to the Ki values of the corresponding thioesters of monocarboxylates. HMG does not affect reductase activity in concentrations of up to 2 mM, yet it greatly enhances the inhibition of the enzyme by des-CoA. Specifically, HMG affects only the Ki value of des-CoA by decreasing it from 1030 microM to 280 microM. The results indicate that reactive cysteine(s) are localized in the catalytic site of HMG-CoA reductase. Within the active site, these cysteines are closely associated with and probably participate in the binding of the CoA moiety of the substrate HMG-CoA. The results are also consistent with the existence of a noncatalytic hydrophobic site in HMG-CoA reductase.